2017
DOI: 10.3390/polym9110559
|View full text |Cite|
|
Sign up to set email alerts
|

Properties of Electrospun Nanofibers of Multi-Block Copolymers of [Poly-ε-caprolactone-b-poly(tetrahydrofuran-co-ε-caprolactone)]m Synthesized by Janus Polymerization

Abstract: Abstract:Novel biodegradable multiblock copolymers of [PCL-b-P(THF-co-CL)] m with PCL fractions of 53.3 and 88.4 wt % were prepared by Janus polymerization of ε-caprolactone (CL) and tetrahydrofuran (THF). Their electrospun mats were obtained with optimized parameters containing bead-free nanofibers whose diameters were between 290 and 520 nm. The mechanical properties of the nanofiber scaffolds were measured showing the tensile strength and strain at break of 8-10 MPa and 123-161%, respectively. Annealing imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
(44 reference statements)
0
14
1
Order By: Relevance
“…Only statistical copolymers had been used in all experiments and it is hard to predict any behaviour and compare it with block copolymers. Some studies for block copolymers can be found for example in [34]. However, we did not find any studies for electrospinning of statistical copolymers.…”
Section: Electrospinning Processcontrasting
confidence: 58%
“…Only statistical copolymers had been used in all experiments and it is hard to predict any behaviour and compare it with block copolymers. Some studies for block copolymers can be found for example in [34]. However, we did not find any studies for electrospinning of statistical copolymers.…”
Section: Electrospinning Processcontrasting
confidence: 58%
“…It has also been reported to be a convenient way to synthesize polymers with various topologies. Diblock poly(THF‐ co ‐CL)‐ b ‐PCL, multiblock [(THF‐ co ‐CL)‐ b ‐PCL] m , branched PTHF, branched poly(THF‐ co ‐CL), and 3‐miktoarm star terpolymers [PEG‐ star ‐PCL‐ star ‐P(CL‐ co ‐THF)] have been successfully synthesized through Janus polymerization simply by using appropriate initiators. Janus polymerization provides researchers with a robust tool to construct topologically well‐defined polymers for a better understanding of structure‐property relationships.…”
Section: Methodsmentioning
confidence: 99%
“…Ling and co-workers [41,100] developed a concept of "Janus polymerization," which combines the incompatible cationic and anionic polymerization mechanisms coexisting in a single growing polymer chain. [101] By employing this "Janus polymerization," a novel Janus macromonomer poly(tetrahydrofuran-cocaprolactone)-b-polycaprolactone (p(THF-co-CL)-b-PCL) with NB functionality was synthesized in one step. [102] Subsequently, Janus-like mixed bottlebrush polymers were obtained by the copolymerization of the resulting Janus macromonomers with norbornenyl-terminated polysarcosine via grafting-through approach ( Figure 5).…”
Section: Grafting-through Approachmentioning
confidence: 99%